2018
DOI: 10.1145/3183506
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human, Legitimate Bot, and Malicious Bot in Online Social Networks Based on Wavelets

Abstract: Social interactions take place in environments that influence people’s behaviours and perceptions. Nowadays, the users of Online Social Network (OSN) generate a massive amount of content based on social interactions. However, OSNs wide popularity and ease of access created a perfect scenario to practice malicious activities, compromising their reliability. To detect automatic information broadcast in OSN, we developed a wavelet-based model that classifies users as being human, legitimate robot, or malicious ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 50 publications
(31 reference statements)
0
6
0
1
Order By: Relevance
“…A wavelet-based approach was introduced by [17]. Specifically, the authors exploited the discrete wavelet transform and extracted a set of features, namely wavelet magnitude, wavelet phase, wavelet domain score, and so on.…”
Section: Related Work a Traditional Machine Learning Algorithmsmentioning
confidence: 99%
“…A wavelet-based approach was introduced by [17]. Specifically, the authors exploited the discrete wavelet transform and extracted a set of features, namely wavelet magnitude, wavelet phase, wavelet domain score, and so on.…”
Section: Related Work a Traditional Machine Learning Algorithmsmentioning
confidence: 99%
“…For example, Subrahmanian et al (2016) suggested a method for identifying "influence bots" that affect Twitter conversations on certain topics. Barbon Jr. et al (2018) proposed a text mining technique to differentiate legitimate from malicious bots. Nevertheless, the application of these methods in policy-oriented empirical research remains very limited.…”
Section: Binary Classification Of Social Botsmentioning
confidence: 99%
“…Stieglitz et al (2017), for example, argued that bots should be further classified based on their goals, with some being categorized as malicious, and others as benign. Consistently, Barbon Jr. et al (2018) argued that some bots should be thought of as legitimate as they are easy for ordinary users to discern, while others who use sophisticated tactics to disguise themselves as humans should be conceptualized as malicious. Others suggested classifying based on context, for example, in the case of political (Gorwa & Guilbeault, 2020;Woolley & Howard, 2018;Yan et al, 2021), news (Lokot & Diakopoulos, 2016), and stock market (Cresci, Lillo, et al, 2019) bots.…”
Section: Introductionmentioning
confidence: 99%
“…Tal abordagem exige o emprego de mão de obra ou envolvimento ativo de uma larga comunidade, e pode não ser a melhor abordagem para analisar grandes volumes de dados [Ferrara et al 2016]. [Jr et al 2018] combinou abordagens comportamentais e análise textual para potencializar a detecção, analisando o tema do texto. Considerou inclusive bots legítimos e suas intenções.…”
Section: Trabalhos Relacionadosunclassified